Contamination and remediation of contaminated firing ranges—an overview - Zhu, Yining; Che, Ruijie; Tu, Biyang; Miao, Jiahe; Lu, Xinya; Li, Jining; Zhu, Yongbing; Wang, Fenghe (Frontiers in Environmental Science, 2024)
Land and groundwater resources are fundamental pillars of sustainable human development. The negligent abandonment of ammunition and its fragments during range activities can result in severe contamination of range sites, thereby posing a significant risk to both the ecological environment and human health. Nevertheless, numerous uncertainties persist regarding the comprehension of range contaminated sites. In this study, the literature on the range of contaminated sites decommissioned after 2000 was systematically examined to consolidate basic information related to these sites, such as contaminant types, contamination status, and remediation measures. Considerable attention is devoted to investigating the advancement of diverse techniques, such as phytoremediation, chemical leaching, and solidification/stabilization, to remediate polluted areas within decommissioned firing ranges. Among the various types of remediation means, physical remediation and chemical remediation have higher remediation efficiency, but generally have higher costs and are prone to secondary pollution. Bioremediation is low cost and environmentally friendly, but has a long restoration cycle. The choice of remediation method should be based on actual needs. Additionally, this study puts forth prospective avenues for future research. Ultimately, this endeavor aims to attract the interest of scholars toward the remediation of contaminated sites within firing ranges, thereby making a valuable contribution to both human well-being and sustainable progress.